Communicating Plastics in Developing Economies: A Comparative Study of Indonesia and Türkiye - Vera Harludi; Emre Yilancik (Institute of Research and Community Outreach - Petra Christian University, 2025)
This research investigates the communication campaign against plastics in the context of environmental communication, offering a comparative analysis between Indonesia and Türkiye. As plastic pollution emerges as a global concern, we conduct a multiple case study analysis on anti-plastic campaigns and policies in both countries. The primary goal is to assess the progress of plastic-related communication efforts. The comparative study leverages the diverse economic, cultural, and regulatory contexts of Indonesia and Türkiye, providing valuable insights into the influence of these factors on environmental communication. The research findings contribute to the development of effective communication strategies and advocate for positive actions in addressing plastic pollution not only in Indonesia and Türkiye but also on a global scale.